Synthesis of Pd-integrated carbon Dot@TiO2 thin film for photocatalytic glycerol reforming reaction for producing hydrogen - Abraham, Athira; Salgaonkar, Kranti N.; Nivedhitha, Thazhath R.; Ekal, Vishal Ashok; Kondhekar, Deepali; Chakraborty, Shubhankar; Gopinath, Chinnakonda S.; Saha, Avishek (Chemistry-an Asian Journal, 2025)
A series of thin-film photocatalysts comprising TiO2 modified with carbon dots (CDs) dispersed either with palladium (Pd-CD/TiO2) or nickel (Ni-CD/TiO2) were synthesized via solid-state and wet-impregnation methods. Morphological characterization (HR-TEM, SEM-EDS) confirmed the anatase phase of TiO2 and the atomic dispersion of metal-integrated CDs on its surface. UV-vis DRS and XPS analyses revealed a marginal red shift in band-gap and the presence of sp2-hybridized graphitic carbon, and metal-carbon interactions, indicating enhanced light absorption and charge separation through Schottky junctions. Under direct sunlight illumination, Pd-CD/TiO2 thin film exhibited superior hydrogen yield (1167 mu mol g-1 h-1) and maintained stability over 25 h, outperforming Ni-CD/TiO2 (494 mu mol g-1 h-1) and bare TiO2 (166 mu mol g-1 h-1) photocatalyst thin films. Concurrent glycerol oxidation at neutral pH (pH similar to 7) yields glycolaldehyde (41% selectivity), formic acid, and dihydroxyacetone as value-added products. Enhanced photocurrent density and lower impedance of Pd-CD/TiO2 corroborate improved charge carrier separation and dynamics. The results demonstrate that Pd-CD synergistically improves the photocatalytic performance of the Pd-CD/TiO2 for sustainable hydrogen generation and selective biomass valorization.
Keywords: Glycerol oxidation; Graphitic carbon dots; hydrogen production; Photocatalysis; titania